KRISTIJONAS DONELAITIS AND GOTTHARD FRIEDRICH STENDER: RETHINKING PARALLELS BETWEEN ENLIGHTENMENT WRITING IN EAST PRUSSIA AND COURLAND - DAIJA, PAULS; BRIEŽKALNE, SANITA (Knygotyra, 2015)
The parallels between Kristijonas Donelaitis (1714–1780) and Gotthard Friedrich Stender (1714–1796) have been analysed in the article by turning attention to similar trends in Enlightenment writing in Protestant regions of Courland and Eastern Prussia. The context of popular enlightenment has been described by exploring similar and different themes in the works by K. Donelaitis and G. F. Stender as well as the 18th century ‘discovery of people’as an European phenomenon. The article consists of four parts, shedding light on the following matters: 1) ethnic and social origins and their role in the reception and heritage of both writers, 2) the siginificance of printed versus oral communication in the dissemination of popular enlightenment ideas; 3) ideological key topics in the works by both writers including the critique of the fashion of foreign trends and different approaches to the past and collective memory; 4) the ideological agenda of enlightenment works including loyalty to one’s social standing as well as synonymous use of ethnic and social denominations in the 18th century. It has been argued in the article that despite the different ways each of the authors carried out their work, parallels between their pioneering activities with regard to Latvian /Lithuanian ‘discovery’ uncovers similar enlightenment agenda inspired by the interest in the ‘common people’ characteristic of the Zeitgeist.
Keywords: Gotthard Friedrich Stender; comparative literature; popular enlightenment; Latvian cultural history; discovery of people